Duodenal obstruction due to two congenital bands: a case report and literature review - Xiong, Shiqiu; Ge, Kuku; Hou, Chongzhi; Yang, Hongbin; Zhang, Hanhua; Zhang, Sheng; Liu, Bailing; Hao, Yuewen; Fang, Ying; Ren, Xiaoxia (Frontiers in Pediatrics, 2025)
IntroductionAnomalous congenital bands are a rare cause of intestinal obstruction, with only five previously reported cases involving duodenal obstruction. We present a fifth case of duodenal obstruction due to two congenital bands and provide a comprehensive literature review summarizing the clinical features of this condition.Case reportAn eight-year-old girl was admitted to our department with recurrent bilious vomiting and abdominal pain lasting six days. She had no significant past medical history, with no previous abdominal surgeries or trauma. Physical examination revealed abdominal tenderness and decreased bowel sounds. Contrast x-ray showed an obstructed passage of contrast through the third part of the duodenum. Abdominal ultrasound identified a strip-like hypoechoic structure compressing the third part of the duodenum. A diagnosis of duodenal obstruction was confirmed, and laparoscopic surgery combined with gastroduodenoscopy was performed. The procedure revealed two congenital bands adjacent to the duodenum: one extending from the duodenum to the transverse colon, and the other from the duodenum to the root of the mesentery. The bands were resected, and gastroduodenoscopy confirmed the resolution of the obstruction.DiscussionWe reviewed 93 cases of anomalous congenital bands, including the present one, comprising 33 adults and 60 children, with 71.0% of the cases involving males. Common symptoms included vomiting and abdominal pain, with physical examinations often showing tenderness and distension. Imaging techniques like plain x-ray, contrast x-ray, ultrasound, and computed tomography often indicated intestinal obstruction but were less effective in directly identifying congenital bands. All cases required abdominal surgery for diagnosis and treatment. Congenital bands were primarily found attached to the ileum or its mesentery and were resected in all cases, with a favorable postoperative prognosis. This case and the literature review provide valuable insights for clinical diagnosis and treatment.